The effect of penicillin administration in early life on murine gut microbiota and blood lymphocyte subsets. (October 2017) - Daniluk, Jaroslaw; Daniluk, Urszula; Rusak, Malgorzata; Dabrowska, Milena; Reszec, Joanna; Garbowicz, Magdalena; Huminska, Kinga; Dabrowski, Andrzej
Abstract: Background and aim: Antibiotics have many beneficial effects but their uncontrolled use may lead to increased risk of serious diseases in the future. Our hypothesis is that an early antibiotic exposition may affect immune system by altering gut microbiota. Therefore, the aim of the study was to determine the effect of penicillin treatment on gut microorganisms and immune system of mice. Methods: 21-days old C57BL6/J/cmdb male mice were treated with low-dose of penicillin (study group) or water only (control group) for 4 weeks. Tissue and stool samples for histology or microbiome assessment and peripheral blood for CBC and flow cytometry evaluation were collected. Results: We found high variability in microbiota composition at different taxonomic levels between littermate mice kept in the same conditions, independently of treatment regimen. Interestingly, low-dose of penicillin caused significant increase of Parabacteroides goldsteinii in stool and in colon tissue in comparison to control group (9.5% vs. 4.9%, p = 0.008 and 10.7% vs. 6.1%, p = 0.008, respectively). Moreover, mice treated with penicillin demonstrated significantly elevated percentage of B cells (median 10.5% vs 8.0%, p = 0.01) and decrease in the percentage of total CD4 + cell (median 75.4% vs 82.5%, p = 0.0039) with subsequent changes among subsets - increased percentage of regulatory T cells (Treg), T helper 1 (Th1) and T helper 2 (Th2) cells. Conclusion: Our study showed significant effect of penicillin on B and T cells in peripheral blood of young mice. This effect may be mediated through changes in gut microbiota represented by the expansion of Parabacteroides goldsteinii. Highlights: Murine gut microbiota is highly variable between littermate mice. Penicillin treatment increases abundance of pathogenic P. goldsteinii bacteria. Antibiotic treatment has a profound effect on the immune system.